Алеф: [роман] / Пауло Коэльо ; [перевод с португальского Е. Матерновской] - Коэльо Пауло (АСТ, 2018)
Экземпляры: (20200217) / Инвентарный номер: 50511 / Цена: 50.00 / Сис.шифр: 84(7Бра)-4 / Авт.знак: К 76 / ГРНТИ: 17.82.31 / ББК: 84(7Бра)-44